Personate legal fact: the theoretical, methodological, and international legal dimension - Тарасов, О. В. (Problems of legality, 2014)
The article is devoted to the study of the legal facts on the ground of legal personology on base of examples from national and international law. The general theoretical definition of a legal fact and classification of personate legal facts have been proposed.